Redefining electrolyte efficiency: bridging the gap with a systematic samarium–copper co-doping approach for optimized conductivity in advanced semiconductor ionic fuel cell - Muhammad Shahid Sharif; Zuhra Tayyab; Sajid Rauf; Muhammad Ahsan Masood; MAK Yousaf Shah; Muhammad Tayyab; Abdullah N Alodhayb; Bin Zhu (Materials Futures)
Significant efforts have been dedicated to developing next-generation optimal electrolytes for high-performance low-temperature solid oxide fuel cells (SOFCs). In this study, we present an innovative co-doping strategy, incorporating samarium (Sm ^3+ ) and copper (Cu ^2+ ) into ceria (Cu _x Sm _0.2- _x Ce _0.8 O _2 , x = 0, 0.05, 0.10, 0.15). By leveraging Sm ^3+ and Cu ^2+ to create oxygen vacancies and Cu ^2+ to further induce the controlled electronic characteristics, we engineered a material with enhanced proton conductivity and efficient electronic transfer and ionic transport. Distribution of relaxation times and electrochemical impedance spectroscopy analyses revealed significantly reduced grain boundary resistance and efficient proton conduction over the temperature range of 320 °C to 520 °C. Notably, the optimized Cu _0.1 Sm _0.1 Ce _0.8 O _2 composition achieved a peak power density of 902 mW cm ^−2 with appreciable ionic conductivity of 0.16 S cm ^−1 at 520 °C, demonstrating its potential as a high-performance electrolyte. UV-Vis analysis indicated a reduced band gap, while DC polarization measurements indicated electronic conductivity of 0.019 S cm ^−1 , suggesting the material possesses semiconducting properties suitable for the electrochemical applications. Advanced physical characterizations and their analysis provided detailed information of the materials, which are suitable for the fuel cell applications. In addition, the post stability of fuel cell device’s characterizations provided the detail information and evident the stable behavior of the as-prepared optimal Cu _0.1 Sm _0.1 Ce _0.8 O _2 (10-CSC) material acted as electrolyte. These findings position Cu _0.1 Sm _0.1 Ce _0.8 O _2 as a promising candidate for intermediate-temperature SOFCs, representing a significant advancement in semiconductor ionic electrolyte materials.